Outsourcing war the just war tradition in the age of military privatization - Eckert, Amy (Cornell University Press, 2016)
In Outsourcing War, Amy E. Eckert examines the ethical implications involved in the widespread use of PMCs, and in particular questions whether they can fit within customary ways of understanding the ethical prosecution of warfare.